Surgical adhesive BioGlue™ does not benefit tendon repair strength: an ex vivo study. (September 2015) - Jordan, M. C.; Schmitt, V.; Dannigkeit, S.; Schmidt, K.; Meffert, R. H.; Hoelscher-Doht, S.
Surgical adhesives are useful supplements in surgery, but their benefit in tendon repair is uncertain. The purpose of this study was to evaluate the effect of BioGlue™ on strength of flexor tendon repair. A total of 60 porcine flexor tendons were divided into three groups. In group one, a conventional core and peripheral suture repair was used. In group two, a core suture and BioGlue™ were used. In group three, a conventional core and peripheral suture repair and BioGlue™ were used. We performed static and cyclic axial load testing and measured diameter of the repair site. We found that BioGlue™ did not improve the tensile strength when added to a core and peripheral suture and that there was an increase in bulk at the repair site. We conclude that BioGlue™ application cannot replace a peripheral suture as tensile strength significantly decreases without a peripheral suture, and it does not benefit a tendon already repaired with a core and peripheral suture. Level of evidence: n/a